PROBLEMATICS OF THE STATUS OF THE MARRIAGE AGREEMENT BEFORE AND AFTER THE DECISION OF THE CONSTITUTIONAL COURT NUMBER 69/PUU-XIII/2015 - Haspada , Deny (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2022)
Marriage agreements made by the prospective bride and groom are usually carried out by the prospective bride and groom a few days before the marriage consent is carried out or the marriage process is legal according to their respective religions and beliefs, made in writing, can be under the hand or authentically. Now, after the Constitutional Court's Decision Number 69/PUU-XIII/2015 dated March 21, 2016, the marriage agreement may be made after marriage is carried out in the sense of having the status as husband and wife. It is an interesting study to investigate the implications of the Constitutional Court's decision and the legal consequences on property status and third parties who feel aggrieved by the existence of the Marriage Agreement. This study uses empirical research using the statute approach and the conceptual approach. The data used is secondary data in the form of primary, secondary and tertiary legal materials. The results showed that the implications of the Constitutional Court's decision on the making of a marriage agreement after marriage made before a Notary changed the legal mechanism for making a marriage agreement which can now be made during the marriage bond by a Notary without having to be preceded by a judge's determination, but Notaries are worried because they have a direct risk and responsibility in making the marriage agreement deed because there is no legal reason for taking refuge based on a Judge's Determination. The legal consequence of making a marriage agreement deed after marriage before the Constitutional Court's decision is a change in the status of husband and wife assets and binding on both parties as well as against third parties. Then after the Constitutional Court's decision, the legal consequences of making a marriage agreement after marriage on the status of inherently joint (closely related) assets must first be made a calculation of the previously mixed assets and the assets to be separated in the marriage bond which will be set forth in the marriage agreement, so that the marriage agreement is made when it is made in the form of an authentic deed, it becomes valid and binding on third parties.